(untitled) (Journal of actual problems of jurisprudence, 2018)
The success of carrying out reforms in Kazakhstan in many respects depends on integration of Kazakhstan into world economic system. At the same time, with liberalization of economic activity the need of providing economic, food security of the republic arises and amplifies. If in modern conditions not to provide elaboration of strategic approaches in issues of economic including food security, prospects of a sustainable development of Kazakhstan at best will be removed on the far future. Tendencies of transnationalization of production of a number of sectors amplify. Information space of Kazakhstan is more and more integrated into a common information space. Key words: Food Security, Legal Support, Veterinary Safety, Sanitary and Epidemiologic Wellbeing.